Studies in Indian history - Panikar, K. M. (Delhi LG Publishers Distributors, 2021)
Included in this volume are three articles and two lectures by the late Sardar K. M. Panikkar mainly on the impact of India, its thought and its culture, on the rest of the world during ancient and medieval times and how, in turn, India was influenced by the outside world.
Keywords: Civilization -- History - History -- IFS as an author -- Indian Foreign Service